Cost-Effectiveness of One-Time Hepatitis C Screening Strategies Among Adolescents and Young Adults in Primary Care Settings. (9th September 2017) - Assoumou, Sabrina A; Tasillo, Abriana; Leff, Jared A; Schackman, Bruce R; Drainoni, Mari-Lynn; Horsburgh, C Robert; Barry, M Anita; Regis, Craig; Kim, Arthur Y; Marshall, Alison; Saxena, Sheel; Smith, Peter C; et al.
Abstract : Risk-based hepatitis C virus (HCV) testing is recommended for young adults. We used simulation modeling to show that routine rapid HCV testing during clinical visits might be cost-effective in settings with a high prevalence of HCV and injection drug use. Abstract: Background: High hepatitis C virus (HCV) rates have been reported in young people who inject drugs (PWID). We evaluated the clinical benefit and cost-effectiveness of testing among youth seen in communities with a high overall number of reported HCV cases. Methods: We developed a decision analytic model to project quality-adjusted life years (QALYs), costs (2016 US), and incremental cost-effectiveness ratios (ICERs) of 9 strategies for 1-time testing among 15- to 30-year-olds seen at urban community health centers. Strategies differed in 3 ways: targeted vs routine testing, rapid finger stick vs standard venipuncture, and ordered by physician vs by counselor/tester using standing orders. We performed deterministic and probabilistic sensitivity analyses (PSA) to evaluate uncertainty. Results: Compared to targeted risk-based testing (current standard of care), routine testing increased the lifetime medical cost by 80 and discounted QALYs by 0.0013 per person. Across all strategies, rapid testing provided higher QALYs at a lower cost per QALY gained and was always preferred. Counselor-initiated routine rapid testing was associated with an ICER of 71000/QALY gained. Results were sensitive to offer and result receipt rates. Counselor-initiated routine rapid testing was cost-effective (ICER <100000/QALY) unless the prevalence of PWID was <0.59%, HCV prevalence among PWID was <16%, reinfection rate was >26 cases per 100 person-years, or reflex confirmatory testing followed all reactive venipuncture diagnostics. In PSA, routine rapid testing was the optimal strategy in 90% of simulations. Conclusions: Routine rapid HCV testing among 15- to 30-year-olds may be cost-effective when the prevalence of PWID is >0.59%.